Elevated temperature micro-impact testing of TiAlSiN coatings produced by physical vapour deposition - Beake, Ben D.; Bird, Andrew; Isern, Luis; Endrino, José L.; Jiang, Feng (Elsevier, 2019)
A high temperature micro-impact test has been developed to assess the fracture resistance of hard coatings under repetitive dynamic high strain rate loading at elevated temperatures. The test was used to study the temperature dependence of the resistance to micro-scale impact fatigue of TiAlSiN coatings on cemented carbide at 25–600 °C. Nanoindentation and micro-scratch tests were also performed over the same temperature range. The results of the micro-impact tests were dependent on the impact load, coating microstructure, coating and substrate mechanical properties, and their temperature dependence. At higher temperatures there was a change in failure mechanism from fracture-dominated to plasticity-dominated behaviour under the cyclic loading conditions. This was attributed to coating and substrate softening.
Keywords: Micro-impact; Fracture resistance; Elevated temperature; Titanium aluminium silicon nitride